1984
DOI: 10.1007/bf00270570
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an X-linked muscular dystrophy in a female due to translocation involving Xp21 and non-random inactivation of the normal X chromosome

Abstract: A young female was diagnosed as having X-linked muscular dystrophy of the Duchenne type. Chromosome studies, including trypsin-Giemsa banding, Quinacrine fluorescence, and nucleolus organizer region (NOR) silver staining revealed an X-autosome reciprocal translocation t(X;21) (p21;p12). Utilizing both [3H] thymidine autoradiography and the BrdU-Hoechst 33258-Giemsa technique, lymphocytes and fibroblasts were found to show a preferential inactivation of the normal X suggesting the presence of a single mutant ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(44 citation statements)
references
References 23 publications
0
40
0
2
Order By: Relevance
“…It is important to note that this region is identical on X-and Y-chromosomes and does not undergo X-inactivation (Blaschke and Rappold 2000). To our knowledge, several different genetic abnormalities have been documented for female DMD and the milder allelic form Becker muscular Dystrophy (BMD): (1) an X-autosome reciprocal translocation and a preferential inactivation of the normal X-chromosome (Verellen-Dumoulin et al 1984); (2) in a classical 45, X0 karyotype of Turner syndrome, simultaneously, the only X-chromosome with a dystrophin mutation (Chelly et al 1986); (3) skewed X inactivation in the normal X-chromosome of the female DMD mutation carriers. (Azofeifa et al 1995); (4) uniparental disomy of female with DMD mutation in both X-chromosome (Quan et al 1997); (5) co-occurrence of mutations in both dystrophin and androgen-receptor genes in the patient (Katayama et al 2006); and (6) girl with homozygous dystrophin mutation caused by consanguinity, whose parents have the same mutations in the DMD gene (Fujii et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that this region is identical on X-and Y-chromosomes and does not undergo X-inactivation (Blaschke and Rappold 2000). To our knowledge, several different genetic abnormalities have been documented for female DMD and the milder allelic form Becker muscular Dystrophy (BMD): (1) an X-autosome reciprocal translocation and a preferential inactivation of the normal X-chromosome (Verellen-Dumoulin et al 1984); (2) in a classical 45, X0 karyotype of Turner syndrome, simultaneously, the only X-chromosome with a dystrophin mutation (Chelly et al 1986); (3) skewed X inactivation in the normal X-chromosome of the female DMD mutation carriers. (Azofeifa et al 1995); (4) uniparental disomy of female with DMD mutation in both X-chromosome (Quan et al 1997); (5) co-occurrence of mutations in both dystrophin and androgen-receptor genes in the patient (Katayama et al 2006); and (6) girl with homozygous dystrophin mutation caused by consanguinity, whose parents have the same mutations in the DMD gene (Fujii et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…At least a dozen females with typical Duchenne muscular dystrophy and X-autosome translocations, involving the middle of the short arm of the X-chromosome, have been described [24,58]. Molecular analysis of these translocations has indicated that the respective breakpoints on the X-chromosome are not strictly identical, but there is now overwhelming evidence that all of them lie within the chromosomal region that gives rise to a large mRNA transcript [ 181.…”
Section: Cloning Genes With Unknown Biochemical Functionmentioning
confidence: 99%
“…The autosome breakpoints were all different. The deduction from these observations is that the Duchenne muscular dystrophy locus lies within this region (Canki~Dutrillaux and Tivadar~1979; Lindenbaum et Jacobs et al, 1981;Zatz et al, 1981;Verellen·Dumoulin et al, 1984)Ĩ n view of this proposal, the field of search for the DMD gene has been narrowed down to the relatively small region around Xp21 in the middle of the short arm of the X chromosome. The most significant advances towards identifying the DMD gene by linkage analysis have come from the use of cloned DNA probes which detect unique sequences mapped by somatic-cell hybrid analysis or in situ hybridization methods to the short arm of the human X chromosome and which, in addition, reveal RFLPs.…”
Section: Reverse Genetics: Duchenne Muscular Dystrophy Como)mentioning
confidence: 99%
“…. Taylor and Muller, 1983) and cloning of the translocation breakpoints (Worton et al, 1984), the mutant sequences responsible should be identified within the next two years.…”
Section: Reverse Genetics: Duchenne Muscular Dystrophy Como)mentioning
confidence: 99%